Somewhere in heaven : the remarkable love story of Dana and Christopher Reeve - Andersen, Christopher P. (New York : Hyperion, 2008)
Traces the inspirational story of the late celebrity couple's early marriage, describing their passionate shared years prior to Christopher's paralyzing accident based on interviews with people who knew them best.
Keywords: Reeve, Christopher, -- 1952-2004.; Reeve, Dana; Actors -- United States -- Biography; Married people -- United States -- Biography